Pengaruh NPM dan ROA Terhadap Perubahan Harga Saham Perbankan Indonesia - Lestari Wuryanti (Universitas Malahayati, 2015)
Abstract. The financial information contained in the company is required to determine the variables -variables that affect stock price changes. This research was conducted in Indonesian banking companies that are in the Indonesia Stock Exchange-listed from 2004 until 2009 with a population of 11 companies. Data analysis was performed with the classical assumption that including normality test, multicollinearity test, autocorrelation test and test heterokesdastisitas. Test data analysis using multiple linear regression, t test and F test multiple linear regression analysis using SPSS 17. Results of multiple linear regression analysis with a confidence level of 5% was obtained respectively the value of the partial coefficient X1 / NPM obtained thitung> t table (2,979> 2,365), Ho is rejected and Ha accepted (no influence between the NPM to changes in stock prices), X2 / ROA obtained thitung <ttable (-1.338 <2.365), Ho accepted and Ha reamed or no effect on stock price changes ROA test results F / test simultaneously by two independent test variables (ratio NPM, ROA) and 1 dependent test variables (Amendment share price) F-test values obtained Concurrent / Simultaneous F count> F table (6,570> 4,35) therefore Ho rejected and Ha accepted, together synchronously / simultaneously a significant influence significant between NPM and ROA ratios) to changes in stock prices.